A factorial emission-focused general equilibrium model for investigating composite effects of multiple environmental policies. (1st August 2021) - Zheng, Xiaogui; Huang, Guohe; Li, Jianyong; Liu, Lirong; Zhang, Xiaoyue; Pan, Xiaojie
Highlights: A factorial emission-focused general equilibrium model is developed. A series of environmental taxes and related subsidies policies are investigated. The composite effects from different environmental policies are explored. The desired wastewater-related policies are identified. Abstract: With the rapid growth of the economy, there are increasing conflicts between economic development and environmental protection. Among these conflicts, the wastewater emission management as one of the significant ways to alleviate water scarcity has been paid increasing attention across the developing countries, such as China. It is thus essential to comprehensively investigate the enviro-economic effects induced by wastewater-related policies. In this study, a factorial emission-focused general equilibrium model (FEGE) is first developed to facilitate examine the composite enviro-economic effects of multiple policy scenarios with regards to wastewater-related environmental taxes and the related subsides. A special case study for the Municipality of Chongqing, China, is conducted to illustrate the potential benefits of its use in the formulation of wastewater-related policies. It is found that the impacts of various wastewater-related policies (i.e., environmental taxes and the related subside) on GDP are different. In detail, green tax policies on GDP are negative, while wastewater emission intensity (WEI) improvement policies on GDP are positive. When green tax reaches 14 yuan/tonne, which is the maximum proposed by the Chinese government, the GDP will drop by 0.37%, which would be deemed acceptable for the Municipality of Chongqing. In addition, the impacts on rural households' consumption are greater than those on urban households' consumption whichever the application of wastewater-related policies; it is because the rural households in the Municipality of Chongqing have a relatively unitary income source. It is thus recommended that the rural household in Chongqing should be paid more attention. For example, some extra allowances could be considered to the rural household to help them cope with the negative economic impacts induced by a new environmental policy. It is expected that the outputs would provide bases for formulating desired wastewater-related policies. Graphical abstract: Image, graphical abstract